Sentidos otorgados a personas trans: una experiencia en San Luis, Argentina (2021)
The enactment of laws in Argentina about dissident gender identity legal guarantees, put inside the academy, the attention for the subject. This article is part of the research Project named Human Rights, Social Control and vulnerable Sectors that belongs to the faculty of Psychology at the San Luis University. Also promotes the divulgation of results about the trans people social representations of the community of San Luis, Argentina. It was used the hermeneutical paradigm to interpret the previously analysis of the information collected. The results indicate thattrans people must conform  to the standards of a binary approach as a social representation, that this population must adapt their identity to the heterosexual model, avoiding their presence in the social space due to the discomfort that they may awake. Other people express social representations of approval, without make any differences because their sexuality, valuing their human condition